On the genus Paralobella (Collembola: Neanuridae: Lobellini) with description of a new Chinese species - Luo, Yongzheng; Palacios-Vargas, José G. (Zootaxa, 2016)
Remarks on the genus Paralobella Cassagnau & Deharveng, 1984 and a key to world species is provided. P. breviseta sp. nov. is described from Eastern China, it is distinguished from all known members of the genus by its biggest size, digitate body dorsolateral and lateral tubercles and very short setae on dorso-internal tubercles.